2006
DOI: 10.1002/jmor.10501
|View full text |Cite
|
Sign up to set email alerts
|

The homology and phylogeny of chondrichthyan tooth enameloid

Abstract: A systematic SEM survey of tooth microstructure in (primarily) fossil taxa spanning chondrichthyan phylogeny demonstrates the presence of a superficial cap of single crystallite enameloid (SCE) on the teeth of several basal elasmobranchs, as well as on the tooth plates of Helodus (a basal holocephalan). This suggests that the epithelial-mesenchymal interactions required for the development of enameloid during odontogenesis are plesiomorphic in chondrichthyans, and most likely in toothed gnathostomes, and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 59 publications
4
96
0
1
Order By: Relevance
“…Studies combining different analytical methods were reported on shark teeth, sometimes on fossilized shark teeth (Daculsi and Kerebel, 1980;Dahm and Risnes, 1999;Frazzetta, 1988;Gillis and Donoghue, 2007;Glas, 1962;Kesmez et al, 2004;LeGeros and Suga, 1980;Moeller et al, 1975;Powlik, 1995;Preuschoft et al, 1974;Reif, 1974;Whitenack et al, 2011. Here we report on a comprehensive study of the chemical composition, the (ultra)structure, and the micromechanical properties, separately for dentin and enameloid, of two shark species (Isurus oxyrinchus, shortfin mako shark; and Galeocerdo cuvier, tiger shark).…”
Section: Introductionmentioning
confidence: 92%
“…Studies combining different analytical methods were reported on shark teeth, sometimes on fossilized shark teeth (Daculsi and Kerebel, 1980;Dahm and Risnes, 1999;Frazzetta, 1988;Gillis and Donoghue, 2007;Glas, 1962;Kesmez et al, 2004;LeGeros and Suga, 1980;Moeller et al, 1975;Powlik, 1995;Preuschoft et al, 1974;Reif, 1974;Whitenack et al, 2011. Here we report on a comprehensive study of the chemical composition, the (ultra)structure, and the micromechanical properties, separately for dentin and enameloid, of two shark species (Isurus oxyrinchus, shortfin mako shark; and Galeocerdo cuvier, tiger shark).…”
Section: Introductionmentioning
confidence: 92%
“…They often have a tissue type called enameloid which seems to consist of elements derived from both dentinal (collagenbased) and enamel (enamelin-based) organic tissues. Indeed, there seems to be a spectrum from 'pure' dentine to 'pure' enamel (see Gillis and Donoghue, 2007, for a review) and the situation is, like much of biology, a bit of a mess. Petrodentine, found in lungfish (Dipnoi) is, however, undoubtedly dentine, but it is most unusual.…”
Section: Lungfishes' Petrodentinementioning
confidence: 98%
“…There are no odontoblast lacunae. The enameloid is up to 50 lm thick and aside from the permeating ondontoblast canaliculi, is structureless, compatible with its interpretation as single crystallite enameloid (SCE) sensu Gillis and Donoghue (2007). The superficial layer of both the scales and the cephalothoracic shield is expanded peripherally by marginal accretion of new tubercles, producing lines of arrested growth.…”
Section: Tesselate Heterostracansmentioning
confidence: 69%